Bioactive glass as a treatment option for dentin hypersensitivity - Luiza Pereira Dias da Cruz; Inger Teixeira de Campos Tuñas (Revista Brasileira de Odontologia, 2018)
Objective: analyze significant information available in the literature regarding DH and its treatment options with a focus on the role of bioactive glass-based toothpastes. Material and Methods: we conducted a literature search of electronic databases, including PUBMed and Scielo, by using the key words: (Dentifrice OR Dentifrices) OR (Toothpaste OR Toothpastes) AND (Treatment) AND (Dentin OR Dentine OR Tooth) AND (Hypersensitivity OR Sensitivity) AND (Dentifrício OR Dentifrícios) AND (Tratamento OR Tratamentos) AND (Dentinária OR Dentina OR Dente) AND (Hipersensibilidade OR Sensibilidade). The papers found were analysed regarding title and abstract contents in order to eliminate the ones that were out of context and not relevant to the review. Results: after this first filter, 31 papers were selected, in which the full text available was considered of good quality and relevant to the context. The languages of the papers were predominantly English and Portuguese and articles published before 2002 were excluded. The use of bioactive glasses in toothpaste formulations has been advocated as a possible solution to managing DH. Conclusion: there are several different options for treating DH, although dentifrices containing bioactive glass are a promising option.